2015
DOI: 10.4012/dmj.2014-138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enamel-bracket bond strength using direct- and indirect-bonding techniques with a self-etching ion releasing S-PRG filler

Abstract: This in vitro study compared the shear bond strength (SBS) and adhesive remnant index (ARI) of two systems for bonding orthodontic brackets to enamel. The first system involved a self-etching primer (Beauty Ortho Bond, BO) containing surface pre-reacted glass filler. The second involved a primer applied with phosphoric acid etching (Transbond XT, TX). Ninety-six extracted human premolars were divided into eight groups: Group I (TX/direct bonding), Group II (TX/indirect bonding), Group III (BO/direct bonding), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 37 publications
(80 reference statements)
4
25
0
1
Order By: Relevance
“…The bond strength of brackets can be effected by the surface preparation techniques, 27 bonding technique, 28 and the type of bonding materials. 29 Similarly, our results demonstrated that the type of bonding agent is important for the shear bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…The bond strength of brackets can be effected by the surface preparation techniques, 27 bonding technique, 28 and the type of bonding materials. 29 Similarly, our results demonstrated that the type of bonding agent is important for the shear bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…The bond strength of brackets can be effected by the surface preparation techniques, 27 bonding technique, 28 and the type of bonding materials. 29 Similarly, our results demonstrated that the type of bonding agent is important for the shear bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced amount of adhesive after debonding (lower ARI) in comparison to AET [17] Lower SBS than AET [17] Legend: TC-thermally cured material; CC-chemo-cured material; LC-light-cured material; SBS-shear bond strength; SET-self-etch technique; AET-acid-etch technique; DB-direct bonding…”
Section: The Beginnings Of the Indirect Technique (1970-1999)mentioning
confidence: 99%
“…This was higher than the gold standard, direct bonding with light-cured composite, which reached a mean value of 13.88 MPa. However, further research did not prove the advantage of Sondhi's resin (Figure 3) [10,16,17]. [ Figure 3.…”
Section: Development Of Bonding Systemsmentioning
confidence: 99%
See 1 more Smart Citation